PENAMBAHAN RAGI ROTI PADA PELLET KOMERSIL TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN SIAM (Pangasius hypophthalmus) - Candra Alfian; Sa’idah Luthfiyah (Jurnal Perikanan Pantura (JPP), 2021)
Siam Patin (Pangasius hypophtalmus) is a freshwater fish commodity of high economic value, but it has constraints in aquaculture that is slow growth and its utilization is less than efficient feed. One of the problem solve is utilization baker’s yeast (Saccaromyces cerevisiae) in the artificial feed. The purpose of this study was to know and observe the effect of the addition of S. cerevisiae to feed on the level of Growth (weigth and Length), and survival rate. The material used is baker’s yeast (S. cerevisiae) which is mixed with sprayed feed and after it is dried, then given as fish feed in culture. The experimental methods with completely randomized design (CRD) were employed in this research. The design consisted of 4 treatments and 3 repepition The treatments tested were K (0 g/kg feed), A (10 g/kg feed), B (20 g/kg feed) and C (30 g/kg feed). The main parameters include weight growth, length growth, and survival rate. The research results showed that the adding baker’s yeast (S. cerevisiae) in the artificial feed were significantly effects (P0,05) on Weight and Length Growth, and survival rate. The best result was in the treatment A (10 g/kg feed) where the best Weight Growth rate of 30.40 (gr/week), Length Growth rate of 0.13 (cm/week), survival rate of 100%.